Maurie Harrison and Mick Roberts interviewed by Rob Willis for the Voices of the bush oral history project - Harrison, Maurie, 1926-; Willis, Rob, 1944-; Harpley, John, 1948-; Roberts, Mick, 1922-2005. (2000)
Folkloric recording. Maurie Harrison, retired orchardist and Kenneth (known as Mick) Roberts, retired barber and cook, sing, play folk songs and recite poetry.
Singing and Music: What a rotten song -- After the ball -- She was a child of the valley -- No, no a thousand times no -- Pyjama song -- Suzie sitting in shoeshine shop -- Beer, beer, glorious beer -- Sister Mary -- My Bonnie (bring back my tucker) -- Are we downhearted -- Recitation: Maurie recites Mrs Jones piano -- Singing and Music: Show me the way to go home -- Mrs Moore, don't have any more -- Music: Pennies from Heaven (piano and violin) -- Old time barn dance (piano and violin) -- Tune (unidentified) -- Schottische (piano and violin) -- Conversation: discussion about fiddle playing technique.
Recorded with John Harpley.
Recorded on Nov. 24, 2000 at Leeton, N.S.W.
Digital master available
Timed summary (1 p.)
Keywords: Harrison, Maurie, -- 1926- -- Interviews; Roberts, Mick, -- 1922-2005 -- Interviews; Folk musicians -- New South Wales -- Leeton; Folk music -- New South Wales -- Leeton; Folk songs -- New South Wales -- Leeton; Folk musicians